Omadacycline successfully treated severe Legionella pneumonia after moxifloxacin treatment failure: Case series - Li, Biyun; Liu, Laiyu; Li, Fei; He, Chunmei; Chen, Yuan; Tian, Xiaodong; Liu, Zhenyu; Zhang, Weizhen (Frontiers in Pharmacology, 2025)
Legionella is a significant pathogen responsible for community-acquired pneumonia and, less commonly, for hospital-acquired pneumonia. Legionella pneumophila, the most prevalent species within the Legionella genus, accounts for 80%–90% of human infections, and often leads to severe pneumonia complicated by multi-organ dysfunction. Omadacycline, a novel tetracycline, has demonstrated in vitro activity against atypical pathogens, including L. pneumophila; however evidence regarding its application in severe Legionella pneumonia remains limited. In this paper, we report 3 cases of successful treatment of severe Legionella pneumonia with omadacycline in patients who initially did not respond to empirical treatment with moxifloxacin, aiming to provide clinical experience and guidance for the use of omadacycline.